Improving partnerships with families and carers in in‐patient mental health services for older people: a staff training programme and family liaison service. Issue 2 (20th February 2012) - Stanbridge, Roger I.; Burbach, Frank R.; Rapsey, Estelle H.S.; Leftwich, Simon H.; McIver, Catherine C.
<x xml:space="preserve">Abstract</x> In spite of policies advocating the involvement of families in the care of mental health service users in the UK, there are few examples of initiatives to develop staff confidence and skills in partnership working. This article describes a whole team training initiative and family liaison service to promote family inclusive working on in‐patient wards for older people in Somerset, UK. A three‐day staff‐training programme is described and training outcomes are reported. Staff report a substantial increase in confidence and family meetings held. A pre‐and post‐ training case note audit shows increased consideration of the needs of families. To further increase face to face meetings with families a family liaison service has been established, whereby a staff member with systemic family therapy training joins ward staff to hold family meetings as part of the assessment/admission process. Evaluation of this service has shown it to be effective with positive feedback from families and staff.